THE IMPACT OF EVA AND MVA ON STOCK RETURNS THROUGH COMPANY VALUE: EVIDENCE FROM INDONESIAN PROPERTY COMPANIES FOR THE 2020–2024 PERIOD - Aulia Syafira Azzahro; Lailatus Sa'adah (Politeknik Negeri Ambon, 2026)
Introduction: This research was intended to examine how Economic Value Added (EVA) and Market Value Added (MVA) influence stock returns, with company value serving as a mediating variable. This research centers on companies within the property sector that are registered on the Indonesian Stock Exchange (IDX) from 2020 to 2024. The property sector was chosen because it has high investment potential, but its performance often fluctuates due to macroeconomic uncertainty and investor perception of the company's value.Methods: A quantitative approach was chosen in this research. There are 92 companies in the population, with the final sample of 10 companies processed from purposive sampling techniques. Data analysis in this research was carried out using classic assumption tests, partial tests, and coefficient of determination tests. In addition, mediation analysis was performed using the PROCESS macro developed by Hayes with the assistance of SPSS 26.Results: The results demonstrate that both EVA and MVA influence the company's value. Market added value, economic added value, and company value do not impact stock returns. After a mediation test using PROCESS macro Hayes, the company's value was unable to mediate between the impact of EVA and MVA on stock returns.Conclusion and Suggestion: This research concludes that both EVA and MVA can be determinants of investor confidence. This emphasizes the importance of companies optimizing their financial performance to increase company value and stock returns. It is advised for future researchers to increase the research object, sample, and observation period to obtain more comprehensive results. It is also recommended to add other variables such as financial value added, good corporate governance, dividend policy, and macroeconomics. Keywords: Economic Value Added, Market Value Added, Company Value, Stock Returns